Biodiversity narratives: stories of the evolving conservation landscape - Louder, Elena; Wyborn, Carina (Environmental conservation, 2020)
Narratives shape human understanding and underscore policy, practice and action. From individuals to multilateral institutions, humans act based on collective stories. As such, narratives have important implications for revisiting biodiversity. There have been growing calls for a ‘new narrative’ to underpin efforts to address biodiversity decline that, for example, foreground optimism, a more people-centred narrative or technological advances. This review presents some of the main contemporary narratives from within the biodiversity space to reflect on their underpinning categories, myths and causal assumptions. It begins by reviewing various interpretations of narrative, which range from critical views where narrative is a heuristic for understanding structures of domination, to advocacy approaches where it is a tool for reimagining ontologies and transitioning to sustainable futures. The work reveals how the conservation space is flush with narratives. As such, efforts to search for a ‘new narrative’ for conservation can be usefully informed by social science scholarship on narratives and related constructs and should reflect critically on the power of narrative to entrench old ways of thought and practice and, alternatively, make space for new ones. Importantly, the transformative potential of narrative may not lie in superficial changes in messaging, but in using narrative to bring multiple ways of knowing into productive dialogue to revisit biodiversity and foster critical reflection.